Paracaecal hernia: a case report on the evolving role of laparoscopy. (2017) - Tayaran, Ammar; Abdulrasool, Haider; Bui, Hai T.
Highlights: Be mindful about pericaecal hernias in patients with distal small intestine obstruction with no prior abdominal surgery. Early laparoscopy can achieve reduction of these hernias without the need of resection. Laparoscopy, in contrast to laparotomy, is associated with quicker recovery. Abstract: A paracaecal hernia, a type of pericaecal hernias, is a rare cause of small intestinal obstruction. Failure of early recognition and reduction of this type of internal hernia may lead to strangulation of the herniated intestine. There has been a number of case reports in the literature about the different types of pericaecal hernias, however the anatomy of these hernias is still poorly understood and the management is still evolving. We are presenting a 75 year old woman, who presented clinically and radiologically with distal small intestinal obstruction. Her past medical history was unremarkable and she had no prior abdominal surgery. After resuscitation, she was taken to the operating theatre for a diagnostic laparoscope, which showed a herniated loop of ileum through a congenital defect in the parietocaecal fold. Reduction of that loop and closure of the peritoneal defect were achieved laparoscopically. Following the procedure, the patient recovered very quickly and she was discharged home within 48 h of her initial admission. Patients with pericaecal hernias tend to present with symptoms of distal small intestinal obstruction. The presence of localised peritonism in the right iliac fossa usually indicate strangulation and that should prompt an urgent surgical intervention. In summary, based on our case, excellent results were achieved from early laparoscopic intervention. Therefore, we recommend early laparoscopy for patients presenting with small intestinal obstruction with no history of abdominal surgery.